Characteristic of different precursor size of activated carbon produced from Oil Palm shell in adsorption of LPG - Mohd Syamsul Hadi; Safarudin G. Herawan; Md Razali, Ayob (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.